Comparison of Feedback based and Non-Feedback Based Protocols for improvement of TCP in MANETs - Deshpande, AS; Kaushal, A (International Journal of Computer Sciences and Engineering, 2025)
Mobile Ad-Hoc Networks (MANETs) have gained a lot of popularity as a means of providing continuous connectivity of network and Internet to mobile computing devices, independent of their physical location. The routing protocols are needed to support the network in such environments. MANETs are used for enhancing the communications with a rapid score of flexibility. The networks will create an interconnection with other connections using IP as the appropriate connecting protocol. Transmission Control Protocol (TCP) is widely applied in the endwise transport layer communication practice. The system has a scheme of self-generating error checks and controls. Its performance is optimum in the wired-networks where packet losses resulting from congestion are experienced. These packet losses could be specifically attributed to the Bit Error Rate (BER) and disconnections during mobility. The application of the standard TCP on this networks will lead to degradation in performance. This paper compares the Feedback Based and Non-Feedback based approaches typically used for improving the TCP protocol performance in MANETs based on secondary data collection methodology.